For all of us, one today an inaugural poet's journey - Blanco, Richard 1968- (Beacon Press, 2013)
"A fluid, poetic memoir anchored by Richard Blanco's experiences as America's fifth inaugural poet In this brief and evocative memoir, Richard Blanco shares his life as a Latino immigrant and openly gay man discovering a new, emotional understanding of what it means to be an American. He tells the story of the call from the White House committee and all the exhilaration and upheaval of the days that followed. He reveals the inspiration and challenges behind the creation of the inaugural poem, "One Today," as well as two other poems commissioned for the occasion ("Mother Country" and "What We Know of Country"), published here for the first time ever, alongside translations of all three poems into his native Spanish. Finally, Blanco reflects on his spiritual embrace of Americans everywhere through the power of poetry and his vision for its new role in our nation's consciousness. Like the inaugural poem itself, For All of Us Today speaks to what makes this country and its people great, marking a triumphant moment in American history and letters"..